2024
DOI: 10.1021/acsnano.3c11601
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer-Dependent Supramolecular Immunosuppressive Modulation for Tissue Reconstruction

Zhixiang Mu,
Tianxi Shen,
Hui Deng
et al.

Abstract: Modulating the properties of biomaterials in terms of the host immune response is critical for tissue repair and regeneration. However, it is unclear how the preference for the cellular microenvironment manipulates the chiral immune responses under physiological or pathological conditions. Here, we reported that in vivo and in vitro oligopeptide immunosuppressive modulation was achieved by manipulation of macrophage polarization using chiral tetrapeptide (Ac-FFFK-OH, marked as FFFK) supramolecular polymers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…As a result, pharmaceutical preparations, such as Thymogen and Thymodepressin, as well as stimulants and suppressors of the immune response, were introduced into clinical practice [77]. A new generation of the Glu-Trp peptide family derivatives as orally active peptidomimetics expresses the same type of activities as the first generation [107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, pharmaceutical preparations, such as Thymogen and Thymodepressin, as well as stimulants and suppressors of the immune response, were introduced into clinical practice [77]. A new generation of the Glu-Trp peptide family derivatives as orally active peptidomimetics expresses the same type of activities as the first generation [107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mu et al showed that the chiral tetrapeptide nanofibers can serve as a defense mechanism in the restoration of tissue homeostasis by upregulating macrophage M2 polarization via the Src-STAT6 axis. And the L-chirality exhibited a more potent effect in inducing macrophage M2 polarization than does the D-chirality, leading to enhanced tissue reconstruction [ 68 ], indicating that chiral materials can promote tissue repair through immunomodulation. Sun et al showed that macrophages exhibited distinct differences in the adhesion and activation behaviors on the different enantiomers’ modified surfaces [ 69 ].…”
Section: Discussionmentioning
confidence: 99%